Pelaksanaan Pembelajaran Bernyanyi Secara Unisono Di Kelas VII-5 SMP Negeri 22 Pekanbaru - Rifa Nabila; Irdhan Epria Darma Putra (Jurnal Indonesia Sosial Teknologi, 2022)
This study aims to describe the implementation of cultural arts learning in unisono singing material. This type of research is qualitative research with a descriptive approach. Data collection techniques through literature studies, observations, interviews and documentation. Data analysis is carried out by classifying primary and secondary data then systematically compiled until conclusions are drawn.The results showed that the implementation of singing learning unisono was not optimal, due to the lack of teacher mastery of the learning implementation plan (RPP). The lack of understanding of teachers' understanding of unisono singing learning so that students are less guided in carrying out singing practices unisono in grades VII-5. The learning strategy used by teachers is Discovery Learning (The ability of students to search so that they can find their own). However, many of the students have not been able to sing unisono in accordance with the established techniques. Due to the lack of mastery of songs owned by students.